Evaluasi Pelayanan Perusahaan Daerah Air Minum (PDAM) Tirta Mangutama dalam Peningkatan Kepuasan Pelanggan (Studi Kasus Kecamatan Kuta Selatan Kabupaten Badung) - Manuartha, I kadek Alit; Pascarani, Ni Nyoman Dewi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2016)
ABSTRACT PDAM Tirta Mangutama is public service who provides managing water clean for community interest in Badung region. PDAM Tirta Mangutama also provides managing water clean in Kuta Selatan, Badung region, which this area having problems within distributed water clean for community. Because of that problems, it is important for increasing public service quality and looking factors and the challenges that inhibitied the better public service quality. In this research, using qualitative descriptive method which is doing data collect with observation and interview also linked with the theory and concept that have been done before. Theory used in this research including public administration theory and focused on service quality concept by Levinne (1990) also customer satisfaction by Freddy Rangkuti (2006). According to Levinne (1990), responsiveness, responsibility, accountability are used for increasing service quality. While according to Freddy Rangkuti (2006) the factors that implied customer satisfaction are value, competitiveness, customer opinions, service stages, and service moments. This factors will be link with PDAM Tirta Mangutama services to customers in Kuta Selatan. The conclusion from this research will be showing that should increasing service quality from PDAM Tirta Mangutama in Kuta Selatan like services for water clean distribution to customers. This is because the services still doesn’t fullfil the demand from around society in Kuta Selatan, so urgently needing for increase service quality became better to customers. Keywords: Public Services, Customer Satisfaction, PDAM Tirta Mangutama